(3GdUeOjI aj Yde GdYQHjIs - (3GdMSjfj, GdeOfj, Ydj NGf Hf CMeOs ((3ehSi Hf MGLj eMeOs)
(3ChdgG (B:s
(3CMSf cdeI jHJOC HgG GdcdGe hNjQ NHQ jNJJe HgG GdeQGe MeOc(B... (3hHYO agPg ahGFO GdUeOjI aj Yde GdYQHjIs
(3BNQgG (B:s
(3hGdTQW hGSe HYOg aYd hGNJUGU HGdEjLGH adG jbGd gd de jbe HNdGa GdgeRI, fMh Gde fTQM dc UOQcs
(3JHUQI GdYfhGf (B:s
(3GdMOjbI GdfOjI aj TQM GdUeOjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdfMhs